Ultrahigh-Bs manganese-zinc soft magnetic ferrite material for PFC (power factor correction) inductor and preparation method of ultrahigh-Bs manganese-zinc soft magnetic ferrite material
By adjusting the ratio of Fe2O3, ZnO and Mn3O4 and adding specific auxiliary components, a multi-step process is used to prepare manganese-zeb soft ferrite material, which solves the problems of low Bs and high loss of existing ferrite materials under high temperature conditions. It achieves the effects of ultra-high Bs and low power loss, and is suitable for PFC inductor applications in the new energy field.
Patent Information
- Application Number
- CN202411691895.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-14
AI Technical Summary
The saturated flux density (Bs) of existing ferrite materials is relatively low under high temperature conditions and have high losses, which is difficult to meet the demand for high Bs and low losses in the new energy field.
The ratio of the main components Fe2O3, ZnO and Mn3O4 is 76.5-79.8 wt%, 8.8-12.3 wt%, and 11.2-11.4 wt%, and the auxiliary components are Ca2CO3, Li2CO3, NiO, V2O5 and Nb2O5, and the specific mixing is carried out. , vibration grinding, prefiring, sand grinding, spray granulation, pressing and sintering processes to prepare manganese zinc soft ferrite materials with ultra-high Bs and low power loss.
Under the 50Hz, 1194A/m test conditions, the saturated magnetic induction intensity of the material is greater than 600mT at 25℃ and greater than 500mT at 100℃. At the same time, the power loss is less than 550kw/m3 and 400kw/m3 at 25℃ and 100℃, respectively, satisfying the High Bs and low loss demand in the new energy field.
Smart Images

Figure BDA0005151177160000071 
Figure BDA0005151177160000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of soft ferrite materials, in particular to an ultra-high Bs manganese-zinc soft ferrite material for PFC inductors and a preparation method thereof. Background Art
[0002] With the continuous miniaturization of electronic products, the corresponding power supplies must be designed with high power density. To achieve high power density of power supplies, the miniaturization and flattening of the magnetic cores in electronic components are key. To achieve the miniaturization and flattening of magnetic cores and the high power density design of power supplies, high Bs and low loss magnetic materials are required.
[0003] The saturation flux density Bs of conventional power ferrite materials at a high temperature of 100°C is generally only about 400mT. Even the high Bs material PC90 launched by TDK has a saturation flux density Bs of 450mT at a high temperature of 100°C, and the loss at 100°C is less than 320kw / m 3 Its Bs value still cannot meet the needs of applications such as the photovoltaic industry and the automotive field that require higher Bs. Currently, most designs use metal magnetic powder cores, and the most widely used is Sendust, which has a high-temperature Bs of about 800mT. However, its core power loss is very high, at 4000kw / m 3 , such high power loss also limits the application of its own high Bs characteristics; therefore, it is even more important to develop a ferrite material with higher Bs and low loss;
[0004] In the field of new energy photovoltaic storage and charging, manganese-zinc power ferrite materials can be used in transformers and PFC inductors. When the power is high, large currents will be generated during operation, and the internal core magnetic components will heat up to around 100°C due to heat. This requires that the manganese-zinc power ferrite material has a very high Bs near the operating temperature of 100°C to prevent core saturation. In addition, due to the high charging power, a ferrite core with a high saturation flux density is required to increase the power density, significantly reduce the size of the charger, and improve charging efficiency.
[0005] Therefore, in order to meet the development needs of various new energy industries, many developers have been researching wide temperature, low loss and high Bs manganese zinc ferrite materials.
[0006] 1. Patent publication number CN112456996A discloses a manganese-zinc ferrite material with high Bs, wide temperature resistance, and low power loss, as well as its preparation method and application. The main components of the material, measured by oxide molar ratio, are Fe2O3: 55.0-57.0 mol%, Mn3O4: 33.5-35.0 mol%, and the balance is ZnO; the trace additives are CaO: 400-800 ppm, Co2O3: 2700-3700 ppm, and NiO: 6000-8000 ppm. The material has low and gentle power loss within the range of 25-100°C, but the Bs at 100°C is only 420 mT, which is relatively low and has limited application range.
[0007] 2. Patent publication number CN107459344A discloses a wide-temperature, low-loss, and high-Bs manganese-zinc ferrite material and its manufacturing method. By improving the material composition and ratio, the prepared material has a second peak temperature of around 100°C, effectively reducing the loss at operating temperature. However, at higher temperatures, the loss degradation caused by high Bs has not been resolved.
[0008] 3. Patent Publication No. WO2023130731A1 discloses a method for preparing a manganese-zinc soft ferrite material. The prepared material has good wide temperature resistance, low power loss, and excellent saturation flux density. However, the Bs of the material at 100°C is 460-465mT, which is still relatively low, and its application range is limited, especially in PFC inductors of switching power supplies.
[0009] 4. Patent publication number CN111039667A provides a wide-temperature, low-loss ferrite and a preparation method thereof, relating to the field of ferrite processing technology. The wide-temperature, low-loss ferrite is composed of a first mixture and a second mixture, and adopts a cooling treatment and a secondary sintering process. The ferrite produced has low power loss values at various temperatures, but the saturation magnetic flux density at a high temperature of 100°C is still relatively low at 422mT, which limits the application range of the material. In addition, the production process of the material requires the first and second mixtures to be produced independently and involves a strong acid corrosion step, which will cause certain operational difficulties in actual production.
[0010] In view of the above situation, it is necessary to improve the existing ferrite materials and the preparation methods thereof so that they can adapt to the current needs for the use of ferrite materials and the preparation methods thereof. Summary of the Invention
[0011] To achieve the above objectives, the present invention provides an ultra-high Bs manganese-zinc soft ferrite material for PFC inductors, comprising a main component and auxiliary components. The main component comprises, by weight percentage, 76.5-79.8 wt% of Fe2O3, 8.8-12.3 wt% of ZnO, and the balance of Mn3O4. The auxiliary components comprise one or more of calcium carbonate, lithium carbonate, nickelous oxide, niobium pentoxide, and vanadium pentoxide, measured in parts per million by mass. The trace additives include 300-800 ppm of Ca2CO3, 500-5000 ppm of Li2CO3, 1000-5000 ppm of NiO, 100-5000 ppm of V2O5, and 200-400 ppm of Nb2O5.
[0012] As a further supplement to the present technical solution, the main components are composed of the following substances in weight percentage: Fe2O3: 76.5wt%; ZnO: 12.3wt%; Mn3O4: 11.2wt%; the auxiliary components are Ca2CO3: 400ppm; Li2C03: 2000ppm; NiO: 2000ppm; V2O5: 400ppm; Nb2O5: 300ppm.
[0013] Further supplementing the technical solution, the main component is composed of the following substances in weight percentage: Fe2O3: 77.2wt%; ZnO: 11.5wt%; Mn3O4: 11.3wt%; auxiliary components are Ca2CO3: 400ppm; Li2C03: 2000ppm; NiO: 2000ppm; V2O5: 400ppm;
[0014] Nb2O5: 300ppm.
[0015] Further supplementing the technical solution, the main component is composed of the following substances in weight percentage: Fe2O3: 78.6wt%; ZnO: 10.4wt%; Mn3O4: 11wt%; auxiliary components are Ca2CO3: 400ppm; Li2C03: 2000ppm; NiO: 2000ppm; V2O5: 400ppm;
[0016] Nb2O5: 300ppm.
[0017] Further supplementing the technical solution, the main component is composed of the following substances in weight percentage: Fe2O3: 79.8wt%; ZnO: 8.8wt%; Mn3O4: 11.4wt%; auxiliary components are Ca2CO3: 400ppm; Li2C03: 2000ppm; NiO: 2000ppm; V2O5: 400ppm;
[0018] Nb2O5: 300ppm.
[0019] Further supplementing the technical solution, the main component is composed of the following substances in weight percentage: Fe2O3: 76.5wt%; ZnO: 12.3wt%; Mn3O4: 11.2wt%; auxiliary components are Ca2CO3: 300ppm; Li2C03: 500ppm; NiO: 5000ppm; V2O5: 500ppm;
[0020] Nb2O5: 200ppm.
[0021] Further supplementing the technical solution, the main component is composed of the following substances in weight percentage: Fe2O3: 76.5wt%; ZnO: 12.3wt%; Mn3O4: 11.2wt%; auxiliary components are Ca2CO3: 500ppm; Li2C03: 1500ppm; NiO: 2500ppm; V2O5: 300ppm;
[0022] Nb2O5: 300ppm.
[0023] A method for preparing an ultra-high Bs manganese-zinc soft ferrite material for a PFC inductor comprises the following steps:
[0024] Step 1: Mix the raw materials consisting of Fe2O3, MnO and ZnO in a strong mixer to make them uniform;
[0025] Step 2: The mixed raw materials are vibrated by a vibration mill to increase the bulk density, and then passed through a flaking machine to form flaky particles and reduce fine powder;
[0026] Step 3: The flaky particles are put into the rotary kiln for pre-firing, and the pre-firing temperature is selected between 900 and 1000℃;
[0027] Step 4: Based on the mass of the pre-burned powder, add the corresponding amount of auxiliary ingredients for sand grinding. Dry the sand grinding slurry and do the particle size test. The D50 is controlled at 0.8-0.95μm and the D90 is controlled at 1.5-2.0μm.
[0028] Step 5: Add PVA to the sand-ground slurry and perform spray granulation to control the bulk density of the granules to 1.35-1.45g / cm 3 ;
[0029] Step 6: The granules obtained by spray drying are pressed into 25*15*8mm green rings by bidirectional pressing, and the green density is controlled at 2.95-3.05g / cm 3 ;
[0030] Step 7: Sintering the green ring pressed in step 6 in a bell furnace at a sintering holding temperature of 1280-1320° C. for 4-8 hours and an oxygen content of 3.5-4.6 vol%. When cooling, the oxygen concentration is kept at the equilibrium oxygen concentration to perform atmosphere protection cooling; finally, a manganese-zinc ferrite sample ring is obtained;
[0031] Step 8: Finally, use the SY-8218 B-H tester at 50Hz, 1194A / m to test the Bs at 25℃ and 100℃, and at 50kHz, 200mT to test the power consumption at 25℃ and 100℃.
[0032] As a further supplement to the present technical solution, the prepared manganese-zinc ferrite material has a saturation magnetic induction intensity Bs greater than 600mT at 25°C under the test conditions of 50Hz and 1194A / m; and a saturation magnetic induction intensity Bs greater than 500mT at 100°C. At the same time, the Curie temperature Tc is ≥300°C.
[0033] As a further supplement to this technical solution, the prepared manganese-zinc ferrite material has a power loss of less than 550kw / m at 50kHz, 200mT test conditions and 25°C. 3 ; At 100℃, the power loss is less than 400kw / m 3 .
[0034] Its beneficial effects are that it has the characteristics of ultra-high Bs and low power consumption; it can fully utilize its high Bs characteristics, is suitable for switching power supply PFC inductors, and the temperature rise can also be met; at the same time, the material cost is much lower than that of metal magnetic powder core materials, avoiding the problem of difficult molding of complex-shaped magnetic cores in the production of metal magnetic powder cores, and can better meet the performance and cost requirements of high-power and high-power density power transformer design. DETAILED DESCRIPTION
[0035] In order to make the technical solution more clear to those skilled in the art, the technical solution of the present invention will be described in detail below with reference to embodiments:
[0036] Example 1:
[0037] Step 1: Mix the raw materials consisting of Fe2O3: 76.5wt%; ZnO: 12.3wt%; Mn3O4: 11.2wt% in a strong mixer;
[0038] Step 2: The raw materials mixed evenly in step 1 are vibrated by a vibration mill to increase the bulk density, and then passed through a slug mill to form flaky particles to reduce fine powder;
[0039] Step 3: The flaked particles are put into the rotary kiln for pre-firing at a temperature of 950°C.
[0040] Step 4: Based on the mass of the pre-burned powder, add the corresponding amount of auxiliary components Ca2CO3: 400ppm; Li2CO3: 2000ppm; NiO: 2000ppm; V2O5: 400ppm; Nb2O5: 300ppm for sand grinding. Dry the sand grinding slurry and perform particle size test. The D50 is controlled at 0.85-0.95μm and the D90 is controlled at 1.5-2.0μm.
[0041] Step 5: Add PVA to the sand-ground slurry and perform spray granulation to control the bulk density of the granules to 1.35-1.45g / cm 3 ;
[0042] Step 6: The granules obtained by spray drying are pressed into 25*15*8mm green rings by bidirectional pressing, and the green density is controlled at 2.95-3.05g / cm 3 ;
[0043] Step 7: Sinter the green ring pressed in Step 6 in a bell-shaped furnace at a holding temperature of 1300°C for 6 hours, with an oxygen content of 4.2 vol%, to obtain a manganese-zinc ferrite sample ring. During cooling, the oxygen concentration was maintained at the equilibrium oxygen concentration under a protective atmosphere.
[0044] Step 8: Use SY-8218 B-H tester at 50Hz, 1194A / m to test Bs at 25℃ and 100℃, and at 50kHz, 200mT to test power consumption at 25℃ and 100℃.
[0045] The formula and test results are shown in Table 1, the same below.
[0046] Example 2:
[0047] The formula is: Fe2O3: 77.2wt%, ZnO: 11.5wt%, Mn3O4: 11.3wt%. The manufacturing process, sintering process and test conditions are the same as those in Example 1.
[0048] Example 3:
[0049] The formula is: Fe203: 78.6wt%; ZnO: 10.4wt%, Mn3O4: 11wt%; the manufacturing process, sintering process and test conditions are the same as those in Example 1.
[0050] Example 4:
[0051] The formula is: Fe203: 79.8wt%; ZnO: 8.8wt%; Mn3O4: 11.4wt%; the manufacturing process, sintering process and test conditions are the same as those in Example 1; the manufacturing process, sintering process and test conditions are the same as those in Example 1.
[0052] Comparative Example 1:
[0053] The formula is: Fe203: 77.5wt%; ZnO: 13.1wt%; Mn3O4: 9.4wt%; the manufacturing process, sintering process and test conditions are the same as those in Example 1; the manufacturing process, sintering process and test conditions are the same as those in Example 1.
[0054] Comparative Example 2:
[0055] The formula is: Fe203: 76.5wt%; ZnO: 12.3wt%; Mn3O4: 11.2wt%; the manufacturing process, sintering process and test conditions are the same as those in Example 1; the manufacturing process, sintering process and test conditions are the same as those in Example 1.
[0056] Comparative Example 3:
[0057] The formula is: Fe203: 75.5wt%; ZnO: 12.1wt%; Mn3O4: 12.4wt%; the manufacturing process, sintering process and test conditions are the same as those in Example 1; the manufacturing process, sintering process and test conditions are the same as those in Example 1.
[0058] Comparative Example 4:
[0059] The formula is Fe2O3: 74.3wt%; ZnO: 11.6wt%; Mn3O4: 14.1wt%; the manufacturing process, sintering process and test conditions are the same as those in Example 1; the manufacturing process, sintering process and test conditions are the same as those in Example 1;
[0060] Comparative Example 5:
[0061] The formula is: Fe203: 80.2wt%; ZnO: 10.5wt%; Mn3O4: 9.3wt%; the manufacturing process, sintering process and test conditions are the same as those in Example 1; the manufacturing process, sintering process and test conditions are the same as those in Example 1.
[0062] Comparative Example 6:
[0063] The formula is: Fe2O3: 81.9wt%; ZnO: 9.8wt%; Mn3O4: 8.3wt%, and the manufacturing process, sintering process and test conditions are the same as those in Example 1. The manufacturing process, sintering process and test conditions are the same as those in Example 1.
[0064] Table 1
[0065]
[0066] Example 5:
[0067] Step 1: Mix the raw materials consisting of Fe2O3: 76.5wt%, ZnO: 12.3wt%, and Mn3O4: 11.2wt% in a strong mixer;
[0068] Step 2: The raw materials mixed evenly in step 1 are vibrated by a vibration mill to increase the bulk density, and then passed through a slug mill to form flaky particles to reduce fine powder;
[0069] Step 3: The flaked particles are put into the rotary kiln for pre-firing at a temperature of 950°C.
[0070] Step 4: Based on the mass of the pre-sintered powder, add corresponding amounts of auxiliary components Ca2CO3: 300ppm; Li2CO3: 500ppm; NiO: 5000ppm; V2O5: 500ppm; Nb2O5: 200ppm for sand grinding. Dry the sand grinding slurry for particle size test. The D50 is controlled at 0.85-0.95μm and the D90 is controlled at 1.5-2.0μm.
[0071] Step 5: Add PVA to the sand-ground slurry and perform spray granulation to control the bulk density of the granules to 1.35-1.45g / cm 3 ;
[0072] Step 6: The granules obtained by spray drying are pressed into 25*15*8mm green rings by bidirectional pressing, and the green density is controlled at 2.95-3.05g / cm 3 ;
[0073] Step 7: The green ring pressed in Step 6 was sintered in a bell-shaped furnace at a holding temperature of 1300°C for 6 hours, with an oxygen content of 4.2 vol%, to obtain a manganese-zinc ferrite sample ring. During cooling, the oxygen concentration was maintained at the equilibrium oxygen concentration under a protective atmosphere.
[0074] Step 8: Use SY-8218 B-H tester at 50Hz, 1194A / m to test Bs at 25℃ and 100℃, and at 50kHz, 200mT to test power consumption at 25℃ and 100℃.
[0075] The formula and test results are shown in Table 2, the same below.
[0076] Example 6:
[0077] The auxiliary components were changed to Ca2CO3: 500ppm; Li2C03: 1500ppm; NiO: 2500ppm; V2O5: 300ppm; Nb2O5: 300ppm; the main components, production process, sintering process and test conditions were the same as those in Example 5.
[0078] Example 7:
[0079] The auxiliary components were changed to Ca2CO3: 500ppm; Li2C03: 3500ppm; NiO: 3000ppm; V2O5: 200ppm; Nb2O5: 400ppm; the main components, production process, sintering process and test conditions were the same as those in Example 5.
[0080] Example 8:
[0081] The auxiliary components were changed to Ca2CO3: 500ppm; Li2C03: 3500ppm, NiO: 3000ppm; V2O5: 200ppm; Nb2O5: 400ppm; the main components, production process, sintering process and test conditions were the same as those in Example 5.
[0082] Comparative Example 7:
[0083] The auxiliary components were changed to Ca2CO3: 500ppm; Li2C03: 3500ppm; NiO: 3000ppm; V2O5: 200ppm; Nb2O5: 400ppm; the main components, production process, sintering process and test conditions were the same as those in Example 5.
[0084] Comparative Example 8:
[0085] The auxiliary components were changed to Ca2CO3: 800ppm; Li2C03: 5000ppm; NiO: 1000ppm; V2O5: 100ppm; Nb2O5: 250ppm; the main components, production process, sintering process and test conditions were the same as those in Example 5.
[0086] Comparative Example 9:
[0087] The auxiliary components were changed to Ca2CO3: 500ppm; Li2C03: 6000ppm, NiO: 3000ppm; V2O5: 300ppm; Nb2O5: 500ppm; the main components, production process, sintering process and test conditions were the same as those in Example 5.
[0088] Comparative Example 10:
[0089] The auxiliary components were changed to Ca2CO3: 200ppm; Li2C03: 1000ppm; NiO: 500ppm; V2O5: 50ppm, Nb2O5: 300ppm; the main components, production process, sintering process and test conditions were the same as Example 5.
[0090] Comparative Example 11:
[0091] The auxiliary components were changed to Ca2CO3: 900ppm; Li2C03: 1000ppm; NiO: 800ppm; V2O5: 600ppm, Nb2O5: 300ppm; the main components, production process, sintering process and test conditions were the same as those in Example 5.
[0092] Comparative Example 12:
[0093] The auxiliary components were changed to Ca2CO3: 1000ppm; Li2C03: 1000ppm; NiO: 5500ppm; V2O5: 800ppm; Nb2O5: 300ppm; the main components, production process, sintering process and test conditions were the same as those in Example 5.
[0094] Table 2
[0095]
[0096] The above technical solutions only reflect the preferred technical solutions of the technical solutions of the present invention. Any changes that may be made to certain parts thereof by those skilled in the art all reflect the principles of the present invention and fall within the scope of protection of the present invention.
Claims
1. An ultra-high Bs manganese-zinc soft ferrite material for PFC inductor, characterized in that: It includes a main component and an auxiliary component; the main component is composed of the following substances in percentage by weight: Fe2O3: 76.5-79.8wt%, ZnO: 8.8-12.3wt%, and the balance is Mn3O4; the auxiliary component is one or more of calcium carbonate, lithium carbonate, nickelous oxide, niobium pentoxide, and vanadium pentoxide, measured in ppm by mass fraction, and the trace additions are Ca2CO3: 300-800ppm; Li2C03: 500-5000ppm; NiO: 1000-5000ppm; V2O5: 100-500ppm; Nb2O5: 200~400ppm.
2. The ultra-high Bs manganese-zinc soft ferrite material for PFC inductor according to claim 1, characterized in that: The main component is composed of the following substances according to weight percentage: Fe2O3: 76.5wt%; ZnO: 12.3wt%; Mn3O4: 11.2wt%; auxiliary components are Ca2CO3: 400ppm; Li2C03: 2000ppm; NiO: 2000ppm; V2O5: 400ppm; Nb2O5: 300ppm.
3. The ultra-high Bs manganese-zinc soft ferrite material for PFC inductor according to claim 1, characterized in that: The main component is composed of the following substances according to weight percentage: Fe2O3: 77.2wt%; ZnO: 11.5wt%; Mn3O4: 11.3wt%; auxiliary components are Ca2CO3: 400ppm; Li2C03: 2000ppm; NiO: 2000ppm; V2O5: 400ppm; Nb2O5: 300ppm.
4. The ultra-high Bs manganese-zinc soft ferrite material for PFC inductor according to claim 1, characterized in that: The main components are composed of the following substances in weight percentage: Fe2O3: 78.6wt%; ZnO: 10.4wt%; Mn3O4: 11wt%; auxiliary components are Ca2CO3: 400ppm; Li2C03: 2000ppm; NiO: 2000ppm; V2O5: 400ppm; Nb2O5: 300ppm.
5. The ultra-high Bs manganese-zinc soft ferrite material for PFC inductor according to claim 1, characterized in that: The main components are composed of the following substances in weight percentage: Fe2O3: 79.8wt%; ZnO: 8.8wt%; Mn3O4: 11.4wt%; the auxiliary components are Ca2CO3: 400ppm; Li2C03: 2000ppm; NiO: 2000ppm; V2O5: 400ppm; Nb2O5: 300ppm.
6. The ultra-high Bs manganese-zinc soft ferrite material for PFC inductor according to claim 1, characterized in that: The main component is composed of the following substances according to weight percentage: Fe2O3: 76.5wt%; ZnO: 12.3wt%; Mn3O4: 11.2wt%; auxiliary components are Ca2CO3: 300ppm; Li2C03: 500ppm; NiO: 5000ppm; V2O5: 500ppm; Nb2O5: 200ppm.
7. The ultra-high Bs manganese-zinc soft ferrite material for PFC inductor according to claim 1, characterized in that: The main component is composed of the following substances according to weight percentage: Fe2O3: 76.5wt%; ZnO: 12.3wt%; Mn3O4: 11.2wt%; auxiliary components are Ca2CO3: 500ppm; Li2C03: 1500ppm; NiO: 2500ppm; V2O5: 300ppm; Nb2O5: 300ppm.
8. A method for preparing an ultra-high Bs manganese-zinc soft ferrite material for PFC inductor according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Mix the raw materials consisting of Fe2O3, MnO and ZnO evenly in a strong mixer; Step 2: The uniformly mixed raw materials are vibrated by a vibrating mill to increase the bulk density, and then passed through a flaking machine to form flaky particles to reduce fine powder; Step 3: The flaky particles are put into the rotary kiln for pre-burning, and the pre-burning temperature is selected between 900 and 1000°C; Step 4: Based on the mass of the pre-burned powder, add the corresponding amount of auxiliary ingredients for sand grinding, dry the sand grinding slurry for particle size test, and control D50 to 0.8-0.95μm and D90 to 1.5-2.0μm; Step 5: Add PVA to the sand-ground slurry and perform spray granulation to control the loose packing density of the granules to 1.35-1.45g / cm 3 ; Step 6: The granules obtained by spray drying are pressed into 25*15*8mm green rings by bidirectional pressing, and the green density is controlled at 2.95-3.05g / cm 3 ; Step 7: sintering the green ring pressed in step 6 in a bell furnace, with the sintering holding temperature at 1280-1320°C, the holding time at 4-8h, the oxygen content at 3.5-4.6vol%, and when cooling, the oxygen concentration is cooled by atmosphere protection according to the equilibrium oxygen concentration; finally, a manganese-zinc ferrite sample ring is obtained; Step 8: Finally, use SY-8218 B-H tester at 50Hz, 1194A / m to test Bs at 25℃ and 100℃, and at 50kHz, 200mT to test power consumption at 25℃ and 100℃.
9. The method for preparing an ultra-high Bs manganese-zinc soft ferrite material for PFC inductor according to claim 8, characterized in that: Under the test conditions of 50Hz and 1194A / m, the saturation magnetic induction intensity Bs of the prepared manganese-zinc ferrite material is greater than 600mT at 25°C; and greater than 500mT at 100°C. Meanwhile, the Curie temperature Tc is ≥300°C.
10. The method for preparing an ultra-high Bs manganese-zinc soft ferrite material for PFC inductor according to claim 9, characterized in that: The power loss of the prepared manganese-zinc ferrite material is less than 550kw / m at 50kHz, 200mT test conditions and 25℃. 3 ; At 100℃, the power loss is less than 400kw / m 3 .
Citation Information
Patent Citations
MnZn ferrite material with wide temperature and low loss and high Bs and manufacturing method thereof
CN107459344A
Wide-temperature-range low-loss ferrite and preparation method thereof
CN111039667A
High-Bs, wide-temperature-range and low-loss power type manganese-zinc ferrite material and preparation method and application thereof
CN112456996A
Method for manufacturing wide-temperature low-loss high-bs manganese-zinc ferrite material
WO2023130731A1
High-temperature high-Bs low-loss MnZn ferrite material and preparation method thereof
CN102219488A